2013
DOI: 10.1371/journal.pone.0070360
|View full text |Cite
|
Sign up to set email alerts
|

First Evidence of Sternal Wound Biofilm following Cardiac Surgery

Abstract: Management of deep sternal wound infection (SWI), a serious complication after cardiac surgery with high morbidity and mortality incidence, requires invasive procedures such as, debridement with primary closure or myocutaneous flap reconstruction along with use of broad spectrum antibiotics. The purpose of this clinical series is to investigate the presence of biofilm in patients with deep SWI. A biofilm is a complex microbial community in which bacteria attach to a biological or non-biological surface and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
(62 reference statements)
1
30
0
1
Order By: Relevance
“…The bacterial burden in postoperative wounds is a major concern because it may necessitate repeated surgical interventions, longer hospital stay, and higher healthcare cost. 23 The use of a silver-coated polyurethane dressing (VAC GranuFoam Ò Silver Dressing; KCI) during NPWT is aimed at infection control. However, it is reported that such a dressing is not effective in delivering silver ions to the wound and most silver is removed by the suction force and found in the wound exudate.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial burden in postoperative wounds is a major concern because it may necessitate repeated surgical interventions, longer hospital stay, and higher healthcare cost. 23 The use of a silver-coated polyurethane dressing (VAC GranuFoam Ò Silver Dressing; KCI) during NPWT is aimed at infection control. However, it is reported that such a dressing is not effective in delivering silver ions to the wound and most silver is removed by the suction force and found in the wound exudate.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also demonstrated that biofilm contributes to wounds associated with mesh infections in the context of abdominal hernia repair [27]. Recently, Elgharably et al evaluated the role of biofilm in sternal wound infections occurring after median sternotomy [5] (see video). The authors prospectively enrolled 6 patients with sternal wound dehiscence and 3 patients without infectious complications having repeat sternotomy for elective cardiac surgery.…”
Section: Clinical Evidence For Biofilm Infection In Woundsmentioning
confidence: 99%
“…30 Elgharably et al provided the first direct evidence of biofilm involvement in human deep sternal wound infection. 49 It has been demonstrated that biofilm impairs key healing processes such as the inflammatory immune response, granulation tissue formation, and epithelialization. 5 Biofilm has been shown to tolerate antibiotics and topical antiseptics in isolation, although multimodal strategies to suppress biofilm were more effective.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Wound biofilm has been documented as emerging in acute wound drains within 2 h after surgery 36 in damaged tendons 37 and in chronic 1,2,33,34 and acute 1,49 wounds. However, there is still a need for further evidence-based knowledge in improving clinical wound or patient outcomes.…”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation